Exploring Domains and Determinants of Early Retirement among School Teachers - Sin, Mun Chong; Koh, Yit Yan; Sin, Kit Yeng (2019)
The retirement age of civil servants in Malaysia was extended to 60 according to Public Service Department Malaysia in 2013. However, lately, early-optional retirement among school teachers has become an issue in which the number of teachers opted for early optional retirement is increasing each year in Malaysia. Employee’s intention for early retirement is influenced by many factors, such as job and organizational, socioeconomic, individual and family situation. Studies show that motivation to leave the teaching profession is related to job satisfaction. However, there is scarce empirical evidence that academicians evaluate the factors causing early retirement among school teachers. This research is set out to explore this issue by identifying factors leading to early retirement among school teachers. Therefore, factors lead to early retirement among school teachers will be identified. The findings come up with a technique for identifying factors of early retirement among school teachers, thereby enable scholars to conduct a more effective and efficient literature review henceforth.